If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3d + -4 = d(d + 8) Reorder the terms: -4 + 3d = d(d + 8) Reorder the terms: -4 + 3d = d(8 + d) -4 + 3d = (8 * d + d * d) -4 + 3d = (8d + d2) Solving -4 + 3d = 8d + d2 Solving for variable 'd'. Combine like terms: 3d + -8d = -5d -4 + -5d + -1d2 = 8d + d2 + -8d + -1d2 Reorder the terms: -4 + -5d + -1d2 = 8d + -8d + d2 + -1d2 Combine like terms: 8d + -8d = 0 -4 + -5d + -1d2 = 0 + d2 + -1d2 -4 + -5d + -1d2 = d2 + -1d2 Combine like terms: d2 + -1d2 = 0 -4 + -5d + -1d2 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(4 + 5d + d2) = 0 Factor a trinomial. -1((4 + d)(1 + d)) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(4 + d)' equal to zero and attempt to solve: Simplifying 4 + d = 0 Solving 4 + d = 0 Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + d = 0 + -4 Combine like terms: 4 + -4 = 0 0 + d = 0 + -4 d = 0 + -4 Combine like terms: 0 + -4 = -4 d = -4 Simplifying d = -4Subproblem 2
Set the factor '(1 + d)' equal to zero and attempt to solve: Simplifying 1 + d = 0 Solving 1 + d = 0 Move all terms containing d to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + d = 0 + -1 Combine like terms: 1 + -1 = 0 0 + d = 0 + -1 d = 0 + -1 Combine like terms: 0 + -1 = -1 d = -1 Simplifying d = -1Solution
d = {-4, -1}
| 44x-4x=5x+18 | | -7-5x=5x+21 | | 10a+8b+4c-8d=7 | | 1-x=0.4 | | x^10=0.6 | | 6/7t=-48 | | 1-(x^10)=0.4 | | 5x-3=13-67 | | 2.8=14/x | | 2(r+5)=10-4r^2 | | 3t^3+5t=-8t^2 | | 2x^2y-5xy^2=0 | | (2x-3)(5x^2-2x+1)= | | z^2-20=22-z | | (-7x^3-2x-4)-(8x^2+4x-7)= | | 2x^2-6x+1=o | | 2p(p+4)=p^2+5p+10 | | 6y-8=40 | | 1/2+4/7p | | x+1.05x=20 | | -3(x+4)=24 | | 13c=2c^2+6 | | 64+x^3=0 | | -15-8b=9b+28 | | 0.5x-0.15=0.15 | | 10a^6/(2a^3) | | -6x+x^2+44.8*0.001=0 | | 0.24-2x=0.38 | | 6x+x^2+44.8*0.001=0 | | 5r(11r+6)=0 | | 4x+3(x-2)=6 | | 6x+7=2x+23 |